Propuesta de plan de negocio para la creación y venta del producto conno crepizz en el sector de Floridablanca Santander (2022)
It is in formulating a business plan for the production and marketing CONNO CREPIZZ, this product will be a different and innovative way to enjoy the traditional ingredients of your pizza and crepes in a special crispy cone. In addition to its comfortable shape for consumption you can assemble your pizza and crepes in the shape of a cone according to your gourmet tastes.